Determinan Harga Saham Perusahaan Telekomunikasi - Christina SE., M.Si (Politeknik Caltex Riau, 2023)
This study aims to examine the effect of liquidity, solvency, activity, and company size on telecommunications company stock prices on the IDX for the 2017-2021 period. The data collection technique is by purposive sampling method so that 40 companies are obtained. Data analysis used in this study is multiple linear regression analysis with the help of SPSS. The results of this study are the variable activity and company size significantly influence stock prices, but liquidity and solvency do not significantly affect stock prices. Simultaneously liquidity, solvency, activity, and company size significantly affect stock prices